DECISION MAKING : Landasan Teologis, Filosofis, Psikologis dan Sosiologis Kepemimpinan Pendidikan di MA Al-Karimiyah - Ahmad Patih (Karimiyah: Journal of Islamic Literature and Muslim Society, 2022)
Decision making is an activity that is usually faced by a leader of an Islamic educational organization or madrasa. Of course, the management of educational units in Islamic boarding schools requires more attention than outside the pesantren, and all policies must be related to the vision and mission of the pesantren. As an educational unit of MA Al Karimiyah education, the participation of pesantren must be involved in all decisions made by the education unit under it, for example the application of eight national education standards. In particular, the principal of MA al-Karimiya madrasa must not only be good and accurate, but also wise in making decisions, taking into account the limitations of different perspectives, methods and perspectives, based on theological, philosophical, psychological and sociological arguments you must. MA Al-Karimiya, as the embodiment of "Al-Muhafadzatu Alal Qodimis Sholih Wal Ahdzu Bil Jadidil Ashhlah", seeks to find educational goals and methods for the future without leaving the past goodness traditions. The relationship that has existed so far is a familial relationship that is obscured by the pesantren system and knowledge which is full of egalitarian values ​​with the sociological principle of 'being good is good'